THE EFFECT OF FAMILY INCOME WITH STUNTING EVENTS IN PRE-SCHOOL CHILDREN AT PUSPA BANGSA KINDER GARTEN SCHOOL BOGOR 2020 : THE EFFECT OF FAMILY INCOME - tisna Tisna Yanti (Jurnal Ilmiah Wijaya, 2020)
Background: One of the nutritional problems that are often encountered in toddlers is stunting. In addition, stunting in children under five is an indicator of nutritional status that can give you an idea disruption overall socio-economic situation in the past. WHO (2017) stated that if the problem of stunting is above 20% it is a public health problem. Globally, an estimated 165 million children under-five years of age, or 25%, were stunted in 2011, while for the Asian level in 2012-2017 Indonesia was ranked the fifth highest stunting prevalence. So that, the purpose of this study was to determine the effect of family income during the COVID-19 pandemic on the incidence of stunting in pre-school children. Method: This type of research is an analytic survey with a cross sectional approach. It means that the researcher conduct obersavtional in nature and are known as descriptive research. The population in this study was 35 respondents. The sample size required was 35 respondents, with a total sampling technique. The instrument in this study was filling out a questionnaire using google form on family income and weight of pre-school children to determine the incidence of pre-school child stunting. Conclusion: The results of univariate analysis for family income variables found that most of the respondents whose family income during the COVID-19 pandemic was in the category less than the Regional Minimum Wage (UMR) /> 4,189,708 million / month, namely 28 respondents (80%) and the results of univariate analysis for incident variables stunting in normal height category 23 (65.7%), very short height category 4 (11.4%) and the results of further statistical analysis obtained p value 0.02, which means there is a relationship between family income and the incidence of stunting in Puspa Bangsa Kinder Garten School, Bogor City.